Synthesis and characterization of novel thin film nanocomposite (TFN) membranes embedded with halloysite nanotubes (HNTs) for water desalination - Ghanbari, M. (2015)
In this study, a new type of thin film nanocomposite (TFN) forward osmosis (FO) membranes was prepared by incorporating different quantities of halloysite nanotubes (HNTs) into the polyamide layer via interfacial polymerization. The FO performance of all fabricated TFN membranes in terms of water permeability and reverse solute flux was compared and the best performing membrane which showed good balance between permeability and solute flux, among all, was selected for further organic fouling investigation. Using 10mM NaCl concentration in feed solution and draw solution of 2M NaCl, the TFN membrane that was embedded with 0.05% HNTs (i.e. TFN0.05) was identified as the best performing membrane due to its high water permeability and low reverse solute flux. Confirmed by the results of BSA removal in the presence of Ca2+, the TFN0.05 membrane also exhibited significantly higher fouling resistance compared to a typical TFC membrane. As an indication to the TFN0.05 fouling reversibility, it was found that >96% permeate flux could be recovered after a simple water rinse process. Overall, it can be concluded that the addition of an appropriate amount of HNTs into the polyamide layer can remarkably improve the antifouling affinity of conventional TFC membranes for FO applications.